Evaluation of the Efficiency of a Soft Dosage Form for the Treatment of Osteoarthritis: Influence on the Level of Pro-inflammatory Cytokines - U. V. Nogaeva; V. E. Kovanskov; D. Yu. Ivkin; E. V. Flisyuk; K. D. Yakimov; E. I. Yeletskaya; E. D. Semivelichenko; V. G. Antonov (Разработка и регистрация лекарственных средств)
Introduction. Osteoarthritis is now considered to be a slowly progressive inflammatory disease that completely affects the joint. An important role in the development of this pathology is played by inflammation of the synovial membrane and ligaments (synovitis), supplemented by constant mechanical stress. Normally, a balance of anti-inflammatory and pro-inflammatory mediators is observed in cartilage, however, under the influence of risk factors, this balance shifts towards the latter.Aim. Evaluation of the effect of a previously developed soft dosage form containing meloxicam, a purine derivative and an immunomodulator M on the level of pro-inflammatory cytokines: IL-1α, IL-1β, IL-6 and TNF-α in osteoarthritis.Materials and methods. The experiment included 25 animals, which were divided into 5 groups by simple randomization: 1 – test (gel 0.5 %), 2 –test (gel 1 %), 3 – reference (Amelotex®, gel 1 %), 4 – control (gel base); 5 – intact. Preclinical modeling of the pathology was carried out by combined injection of 0.1 ml of a mixture of complete Freund's adjuvant with a 10 % suspension of talc in isotonic sodium chloride solution in a ratio of 1 : 10 into the cavity of the hock (tarsal) joint of Brown Norvay Catholic Rats male rats. Enzyme immunoassay of animal blood serum on the 28th day of the experiment was performed using standard ELISA plate kits (Cloud-Clone Corp., USA). Statistical data processing was performed using GraphPad Prism 8.0.2 software (GraphPad Software Inc., USA), differences were considered statistically significant at p < 0.05.Results and discussion. The developed compositions contributed to a decrease in the level of pro-inflammatory cytokines (IL-1α, IL-6 and TNF-α) compared with the main and reference gel preparation. At the same time, differences were found between the effect observed from the use of the test agents (gel 0.5 %, gel 1 %) and the reference drug in terms of the effect on the level of IL-1α and TNF-α, which indicates a greater effectiveness of the selected combination of active substances, because, unlike the single-component gel Amelotex®, the compositions developed by us additionally included a purine derivative and an immunomodulator M. The data obtained are important from the point of view of understanding the mechanism of action of a soft dosage form.Conclusion. Based on the results of previous and present studies, it is assumed that the combined composition of the soft dosage form with a half (0.5 %) concentration of meloxicam is of greatest interest for clinical practice, since its use at a high level of effectiveness additionally reduces the likelihood of adverse reactions from the non-steroidal anti-inflammatory drug, which is important in the case of long-term therapy of osteoarthritis.